Synthesis, spectral characterization and crystal structure of a noveltrinuclear di-n-butyltin(IV) complex with pyruvic acid-N(4)-cyclohexylthiosemicarbazone (H2PACT) - M.A., Salam; M.A., Affan; Fasihuddin B., Ahmad; Ismail, Jusoh; Mustaffa B., Shamsuddin; Bohari, Yamin; Farina, Yang (ScienceDirect, 2012)
A new trinuclear di-n-butyltin(IV) complex with pyruvic acid-N(4)-cyclohexylthiosemicarbazone (H2PACT) ligand was synthesized and characterized by elemental analyses, molar conductivity, UV–Vis, FT-IR, 1H, 119Sn NMR spectroscopy and single crystal X-ray study. Single crystal X-ray diffraction data revealed that this complex was trinuclear cyclic fashion with the pyruvic acid-N(4)-cyclohexylthiosemicarbazone ligand. In the trinuclear di-n-butyltin(IV) complex, the ligand (H2PACT) is coordinated to the central tin(IV) atoms via the carboxylato-O, the azomethine-N and the thiolato-S atoms. The trinuclear tin system is formed by the bridges through the carbonyl oxygen atom of the carboxylate moieties and making the tin atom of seven coordinated in distorted pentagonal bipyramidal geometry. Single crystal X-ray data indicates that the complex (1) crystallized in cubic system with space group I-43d, a = b = c = 30.3273(17) Å, α = β = γ = 90°, Z = 16, μ(MoKα) = 1.209 mm−1, F(000) = 12,144, and final R1 = 0.0390, wR2 = 0.0843 for observed reflections 4582(I > 2σ(I)).